Dampak Inovasi Teknologi Keuangan Publik Terhadap Akuntabilitas Dan Transparansi: Sebuah Kajian Literatur - Dwinanda, Fathur Rahman; Muharam, Riki Satia; Miftah, Ahmad Zaini; Firmansyah, Anry; Komara, Syifa Rachmania (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2023)
On a global scale, advances in public finance technology have played a central role in improving efficiency, accountability and transparency in public financial management. Public finance technology innovation, particularly in the form of fintech, has proven itself to be an effective tool in reducing reliance on manual processes, creating efficiencies that cover various aspects of public finance. Nonetheless, challenges still come with the implementation of public finance technology innovation. The research method uses the literature review method which is one of the qualitative research methods. In this research, the author collects and analyzes existing information in scientific literature to provide a deeper understanding of the impact of public finance technology innovation on accountability and transparency in public financial management. Innovative initiatives, such as e-procurement, e-budgeting, e-audit, and fintech, have been successfully implemented in various countries, including Indonesia, with the aim of improving efficiency, transparency, and accountability in the public finance system. Nonetheless, a number of challenges that need to be overcome were identified.